ABUNDANCE OF MAJOR PESTS OF BANANA UNDER SOUTH GUJARAT AGRO-CLIMATIC CONDITIONS - SHUKLA, ABHISHEK; PATEL, Z.P.; SAXENA, S.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Banana (Musa paradisica L.) is the second important fruit crop grown in South Gujarat. This crop is attacked by different insect pests under South Gujarat conditions. The roving survey was conducted during 2007-08 and 2008-09 to know the status of insect pests of banana. The results showed that the infestation of banana aphid (Pentalonia nigronervosa Coq.) was observed during September to February. As high as 28.26 and 25.84 per cent pseudosuckers were infested by the pest during the month of February. Lace wing bug (Stephanitis typcus) was observed during May to October. Its population was highest in June-July in both the years of survey. The tobacco caterpillar, podoptera litura (Fab.) and semilooper (Chrysodeixix acuta) were confined to monsoon i.e. June to October, which was much conceding with the early crop stage. The infestation of scale insect remain negligible (below 1 per cent), while the infestation of mealybug was highest in February. The mite (Roalia indica) infestation recorded throughout the year with maximum i.e. 6.45 and 2.27 per cent leaves infested in the month of February.